Criminal Liability of Debt Collectors in the Execution of Fiduciary Guarantees with Fraud Mode After the Constitutional Court Decision Number 18/PUU-XVII/2019 - Rommy Igrisa; Subekti Subekti (Rechtsvinding, 2026)
The execution of fiduciary guarantees by debt collectors frequently gives rise to legal problems, particularly when such execution is carried out through fraudulent practices. Following the Constitutional Court Decision Number 18/PUU-XVII/2019, fiduciary execution may no longer be conducted unilaterally unless the debtor voluntarily surrenders the collateral object. Nevertheless, in practice, debt collectors have shifted their modus operandi from physical coercion to more subtle forms of deception in order to obtain fiduciary objects. This research aims to analyze the criminal liability of debt collectors who execute fiduciary guarantees through fraudulent means and to examine the application of criminal law to such practices. The study employs a juridical-empirical research method, combining statutory analysis with field data obtained through interviews with debtors, debt collectors, and representatives of finance companies, as well as observations of fiduciary execution practices. The findings indicate that fraudulent acts committed by debt collectors such as impersonating finance company officers, providing false information, and making deceptive promises fulfill the elements of fraud as stipulated in Article 378 of the Indonesian Criminal Code. Moreover, such actions violate the Fiduciary Security Law and the Constitutional Court’s ruling, thereby giving rise to individual criminal liability and potential corporate liability when finance companies fail to exercise proper supervision. This study concludes that stricter law enforcement and enhanced legal awareness are necessary to protect debtors’ rights and ensure lawful fiduciary execution practices.